Entre toadas e memórias: história e cultura dos vaqueiros de Lagoa do Ouro - PE (1957-2014). - Gonçalves, Jairo de Lucena (2020)
The present study had the objective of creating a version about the History and Culture of the cowboys in the Municipality of Lagoa do Ouro - PE, from the second half of the 20th century. Methodologically, we use research practices in Oral History, developed in the papers of Guimarães Neto (2006). Regarding the theoretical foundations, we used the studies of Alberti (2000) who sees Oral History as a method and established dialogues with the Social Sciences, with Clifford Geertz (2011) and Hall (1997). Thus, our theoretical contribution starts from the principle of interdisciplinarity, grouping the discussions of cultural and social historians, linguists, geographers and anthropologists throughout the work. In the composition of sources for the construction of these narratives, we use periodicals (especially the Diário de Pernambuco), in addition to documents issued by official bodies (Official Gazette of the State of PE), photographs and reports of memories, which are the fundamental raw materials of analysis, which seeks to know the work of the first cowboys and careers, their social relations and cultural expressions.